2010
DOI: 10.1161/strokeaha.109.567735
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis and the Risk of Ischemic Stroke

Abstract: Background and Purpose-The aim of this study is to estimate the risk of ischemic stroke during a 3-year follow-up period after a tuberculosis diagnosis using a nationwide, population-based study and a retrospective cohort design. Method-The study cohort comprised 2283 patients who had received treatment for tuberculosis, except tuberculosis of the meninges and central nervous system, between 2000 and 2003; 6849 randomly selected subjects comprised the comparison cohort. Cox proportional hazard regressions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 37 publications
3
92
1
1
Order By: Relevance
“…In a longitudinal study, 6% of non CNS tuberculosis patients and 3.7% of controls developed stroke. The hazard ratio of ischemic stroke for tubercular patients in a 3 year follow up was 1.52 times higher compared to nontubercular patients [9]. In this study the patients with TBM were excluded.…”
Section: Magnitude Of the Problemmentioning
confidence: 81%
See 2 more Smart Citations
“…In a longitudinal study, 6% of non CNS tuberculosis patients and 3.7% of controls developed stroke. The hazard ratio of ischemic stroke for tubercular patients in a 3 year follow up was 1.52 times higher compared to nontubercular patients [9]. In this study the patients with TBM were excluded.…”
Section: Magnitude Of the Problemmentioning
confidence: 81%
“…In the year 2007, the worldwide estimate of tuberculosis was 9.27 million new cases and 1.78 million deaths [7]. A link between tuberculosis, atherosclerosis and stroke has been suggested which sometimes correspond with central nervous system (CNS) tuberculosis [8,9]. In a longitudinal study, 6% of non CNS tuberculosis patients and 3.7% of controls developed stroke.…”
Section: Magnitude Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Esse fato pode ocorrer pelo possível agravamento das doenças do aparelho circulatório pela TB 19 . Apesar de reconhecida a associação entre TB e diabetes, pelo agravamento da TB por este agravo ou vice-versa 20,21 , não se observou relação na análise aqui realizada.…”
Section: Discussionunclassified
“…In the subgroup analyses performed in the present study, isolated OCNP was identified as an independent risk factor for stroke even after adjusting for patient age and the presence of common cardiovascular risk factors such as HTN, diabetes, etc. Other possible mechanisms have been proposed, and these include roles for inflammation, infectious processes and hypercoagulability [6,8,25,26,27]. These factors were not evaluated in the present study, but would be factors to consider in future studies.…”
Section: Discussionmentioning
confidence: 98%